EFEKTIVITAS PENDIDIKAN KESEHATAN BERDASARKAN HEALTH BELIEF MODEL TERHADAP PENGETAHUAN DAN KESADARAN DIRI PASIEN TENTANG PERAWATAN KAKI DIABETES - Ilham Dani Firdaus; Yesi " Hasneli N; Herlina " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   The purpose of the research was to identify the effectivity of health education based on Health Belief Model to patient knowledge and self awareness about diabetic foot care. The research used quasy experiment design with non-equivalent control group design that divided into  experimental and control group. Samples of the research were 34 people that divided into experiment and control group. Samples taken by using purposive sampling technique which selected besed on the inclusion criteria. Data collection’s tool in this research knowledge and self awareness. The experimental group were given health education based on the Health Belief Model. Data analyzed with univariate and bivariate, using wilcoxon and mann whitney. The results of the research showed that mean level of knowledge before intervention was 5.76, and after was 13.88 (p value = 0.000), while the mean self consciousness before intervention was 12.41, and after was 17.35 (p value = 0.000). It means that there was is an increasing knowledge and self awareness about diabetic foot care of the patient and health education based on Health Belief Model could increasing patient’s knowledge and self awareness. The results of this research recommend that health education based on Health Belief Model could be part of nursing intervention to increase patient’s knowledge and self awareness about diabetic foot care. Keywords: Diabetic foot care, Health Belief Model, knowledge, self awareness.